Benefits of dense labour markets: Evidence from transitions to employment in Germany - Silke Hamann; Annekatrin Niebuhr; Cornelius Peters (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
We analyse whether the size of the local labour market allows for better matching between job seekers and vacancies, which is thought to enhance productivity. This analysis is based on a large data set providing detailed micro-level information on new employment relationships in Germany. Our results suggest rather small matching benefits. Doubling employment density increases the productivity of new employment relationships by 1.1% to 1.2%. Moreover, the findings indicate that the benefits accrue only to persons experiencing job-to-job transitions and short-term unemployed. We detect no important impact of agglomeration on transitions from long-term non-employed. – – Wir untersuchen, ob die Größe des lokalen Arbeitsmarktes die Qualität von Matches zwischen Arbeitsuchenden und offenen Stellen verbessert, welches sich in einer höheren Produktivität widerspiegeln sollte. Die Analyse basiert auf einem umfangreichen Individualdatensatz mit detaillierten Informationen zu einzelnen Beschäftigungsaufnahmen in Deutschland. Unsere Ergebnisse deuten auf eher geringe Matchingvorteile hin. Eine Verdoppelung der Beschäftigungsdichte erhöht die Produktivität neuer Beschäftigungsverhältnisse um 1,1% bis 1,2%. Allerdings profitieren den Resultaten zufolge ausschließlich Personen mit einem Job-to-Job Wechsel oder einer Beschäftigungsaufnahme nach einer kurzen Beschäftigungsunterbrechung. Die Produktivität nach einer langen Beschäftigungsunterbrechung wird nicht von der Dichte des lokalen Arbeitsmarktes beeinflusst.
Keywords: R23; J31; 330; agglomeration economies; matching; urban wage premium; transitions to employment